Factors governing irrigation water productivity of rice in northwestern India: evidence from farmers’ fields - Deb, Proloy; Urfels, Anton; Kumar, Virender; Veettil, Prakashan Chellattan; Srivastava, Amit Kumar; Dubey, Swatantra Kumar; Peramaiyan, Panneerselvam; Singh, Sudhanshu; Rawal, Sandeep; Kumar, Satyendra; Garg, Rajbir; Kamboj, Baldev Raj; et al. (Elsevier, 2025)
Northwestern India is a global groundwater depletion hotspot, with intensive agricultural water use causing an average groundwater table decline of ∼0.4m per year. Farmers typically cultivate rice during the monsoon (kharif) season under puddled flooded conditions, driven by subsidized electricity and government assured minimum support prices for cereals crops. Research trials show mechanized dry-direct seeded rice (DSR) significantly reduces water use without compromising yields. However, evidence of irrigation water savings and improved irrigation water productivity (IWP) under farmers' practice remains limited. To investigate this, we installed 100 water flowmeters in farmers’ fields, measuring seasonal water use and conducted group interviews to assess production practices and yields for DSR and puddled transplanted rice (PTR) fields. DSR showed higher rice yields and significantly greater IWP than PTR. Additionally, we found irrigation water application (IWA) in DSR to be only slightly lower than PTR, but remained 1.6–2 folds higher than research trials, indicating substantial potential for further reductions. Key drivers of water use differed substantially among DSR and PTR, with shifts in sowing dates offering further water-saving opportunities and number of wells in a village constraining irrigation. Importantly, farmers adopting DSR reported shifting from double cropping (rice-wheat) to triple cropping (rice-potato-wheat, rice-wheat-maize) to increase incomes, potentially offsetting water savings. Overall, DSR improves IWP and farmers can further reduce IWA through trainings on irrigation scheduling, freeing up electricity resources and government subsidies. However, technological solutions alone cannot resolve the groundwater crisis – system-wide policies balancing farmer incomes and water conservation will be essential.